Performance of Magneto Hydro Dynamic (MHD) as a Power Generation Support Tool - Purwati W, Wiwik; Atmojo, Slamet Priyo; Margana, Margana; Suwarti, Suwarti; Prasetiyo, Budhi; Khoiroh, Ikhwatinah (Eksergi, 2022)
Magnetohydrodynamics is a method for generating electricity by utilizing the interaction between a magnetic field and an electrolyte fluid. MHD components: salt water electrolyte, Neodymium N52 magnet, and Cu-Zn electrode. The MHD used is a coarse salt water electrolyte. The purpose of the MHD model is as an innovative technological breakthrough that is used to support increasing the efficiency of the power generation system. The lowest efficiency is shown in the second data with variations in salt content of the 5 grams/liter experiment without MHD support, which is 0.08%. The highest efficiency is shown in the twentieth data with variations in salt content of the 95 gram/liter experiment supported by MHD, which is 0.59%. The maximum efficiency increase that can be achieved is 0.37% with variations in salt content of 60 grams/liter.